2006
DOI: 10.1093/jaoac/89.5.1403
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Benzimidazole Fungicides in Soil Samples Using Microwave-Assisted Micellar Extraction and Liquid Chromatography with Fluorescence Detection

Abstract: A simple and fast analytical method was developed for the determination of benzimidazole fungicides (benomyl, carbendazim, thiabendazole, and fuberidazole) in soil samples. The analytes were extracted from the soil samples by means of conventional microwave-assisted extraction, using the non-ionic surfactants polyoxyethylene 10 lauryl ether (POLE) and oligoethylene glycol monooalkyl ether (Genapol X-080) as extractants. Determinations were made by using liquid chromatography with direct fluorescence detection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…High performance liquid chromatography (HPLC) with ultraviolet (UV), 6,9,10 fluorescence (FL) detection 11,12 and mass spectrometry (MS) 4,[13][14][15] have been accepted as popular and powerful tools for the analysis of benzimidazoles. Although the MS detector provides more sensitivity and selectivity than the UV for monitoring target compounds in complex samples, it is a very expensive and complex instrument.…”
Section: Introductionmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC) with ultraviolet (UV), 6,9,10 fluorescence (FL) detection 11,12 and mass spectrometry (MS) 4,[13][14][15] have been accepted as popular and powerful tools for the analysis of benzimidazoles. Although the MS detector provides more sensitivity and selectivity than the UV for monitoring target compounds in complex samples, it is a very expensive and complex instrument.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, benzimidazole fungicides reside in soil; benomyl metabolite carbendazim has reproductive toxicity; and Usman et al found that the long-term use of procymidone and fludioxonil could lead to increased resistance [ 44 ]. Chechi et al found that if these fungicides were not applied scientifically, they could induce resistance in C. fructicola [ 45 , 46 , 47 ]. Natural agents have attracted attention because phytochemicals have advantages that can potentially control plant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of chemical fungicides not scientific and rational result residue, resistance, environmental pollution and other problems [ 7 ], Halko et al indicated that benzimidazole fungicides residue in soil, Gabriel et al determined residue levels of seven commonly used pesticides and suggested long-term exposure can still cause health risks. Lim et al studied and reported that the benomyl metabolite carbendazim has reproductive toxicity, Younghae et al found that if applied unscientifically, which can lead to fungicide resistance in F. fujikuroi [ 8 , 9 , 10 ]. In contrast, natural products, such as natural product and antagonistic microbes, have the advantages of low toxicity, cause no pollution, and do not easily lead to pesticide resistance.…”
Section: Introductionmentioning
confidence: 99%